Patient Satisfaction Level on Effect of Treatment Duration at Prima Medan Royal Hospital - Lubis, Nurul Sri Finna; Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Suyono, Tan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Waiting time in patient care the treatment is a problem that often causes patient complaints in various health institutions. The time a patient remains at registration, examination, and drug taking reflects how the agency manages the service component tailored to the patient's situation and expectations. This research aims to see the waiting time with patient satisfaction. This study uses a research design analytic observational with a cross-sectional study approach conducted at the hospital Royal prima. The sampling technique uses purposive sampling with as many as 170 respondents. Analysis test with chi-square test with a significance level of p < 0.05. From the chi-square test results, the waiting time for registration and examination drug on patient satisfaction obtained p value = 0.000 and 0.021 <0.05 means Ho is rejected and Ha accepted, implying a relationship between the waiting time for registration and inspection with patient satisfaction. Meanwhile, the time of taking the drug on patient satisfaction is obtained p value = 0.400> 0.05 means Ho is accepted and Ha is rejected, meaning there is no relationship between the time Wait for taking medication and patient satisfaction. So, it is recommended that officers be more committed and disciplined in providing appropriate services with a predetermined schedule.